2011
DOI: 10.2190/tw.41.3.e
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Banking and Financial Products: A Comparative Study of Chinese and American Practices

Abstract: This study examines the visual rhetoric used in Chinese and American promotional business communication. Comparing banking and financial product brochures published in the two countries, the study finds similar as well as different visual strategies. Most importantly, the Chinese samples frequently use visual metaphors, whereas the American samples hardly do. Prompted by this finding, I review relevant literature on visual metaphors and examine their structures and rhetorical functions. In addition, the study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
3
2
0
Order By: Relevance
“…Fukuoka et al (1999) suggested that such cartoon pictures in Asian manuals help to make difficult tasks seem like fun and to create a friendly atmosphere. Yu (2011) arrived at similar conclusions in the completely different genre of advertisements for banking and financial products. The comprehensive content analysis by Li et al (in press) confirmed these general tendencies, stating that Chinese manuals include more visuals with an entertaining function, while Western manuals tend to limit themselves to entirely instrumental visuals.…”
Section: Earlier Studies and Research Hypothesessupporting
confidence: 54%
See 2 more Smart Citations
“…Fukuoka et al (1999) suggested that such cartoon pictures in Asian manuals help to make difficult tasks seem like fun and to create a friendly atmosphere. Yu (2011) arrived at similar conclusions in the completely different genre of advertisements for banking and financial products. The comprehensive content analysis by Li et al (in press) confirmed these general tendencies, stating that Chinese manuals include more visuals with an entertaining function, while Western manuals tend to limit themselves to entirely instrumental visuals.…”
Section: Earlier Studies and Research Hypothesessupporting
confidence: 54%
“…(1999) suggested that such cartoon pictures in Asian manuals help to make difficult tasks seem like fun and to create a friendly atmosphere. Yu (2011) arrived at similar conclusions in the completely different genre of advertisements for banking and financial products. The comprehensive content analysis by Li et al.…”
Section: Earlier Studies and Research Hypothesessupporting
confidence: 54%
See 1 more Smart Citation
“…Fukuoka et al (1999) suggested that such cartoon pictures in Asian manuals help to make difficult tasks seem like fun and to create a friendly atmosphere. Yu (2011) came to similar conclusions in the completely different genre of advertisements for banking and financial products. The comprehensive content analysis (Chapter 2) confirmed these general tendencies, stating that Chinese manuals include more visuals with an entertaining function, while Western manuals tend to limit themselves to entirely instrumental visuals.…”
Section: Earlier Studies and Research Hypothesessupporting
confidence: 56%
“…These findings suggest that cross-cultural document design practices regarding the selection of visuals (the study reported in Chapter 2; Barnum & Li, 2006;Fukuoka et al, 1999;Q. Wang, 2000;Yu, 2011) may reflect what users actually prefer. This is in contrast to cultural differences regarding structure: The study described in Chapter 4 did not find such a clear connection between the structural differences in manuals found in content analyses and the task performance and appreciation of users.…”
Section: Main Findingsmentioning
confidence: 93%